Validation of a mathematical procedure for the cobb angle assessment based on photogrammetry - Navarro, Isis Juliene Rodrigues Leite (2019)
This prospective study aimed to assess the concurrent validity and diagnostic accuracy of a mathematical procedure for measurement of the spinal inclination angle, analogous to the Cobb angle, by means of photogrammetry. Methods Sixty-one subjects (aged 7 to 18 years), male and female, underwent radiographic (Cobb angle) and photogrammetric (DIPA [Digital Image-based Postural Assessment] angle) evaluations. The measurement of spinal inclination angle obtained through photogrammetry followed the Digital Image-Based Postural Assessment software protocol. Concurrent validity was appraised using Spearman rank correlation, the coefficient of determination, the root-mean-square error, Bland-Altman plot analysis, and receiver operating characteristic analysis, adopting P ≤ .05. Results The analyses were divided according to the topography of the scoliotic curve (thoracic, lumbar, or thoracolumbar). The correlations were excellent (from 0.72 to 0.81) and significant for all the regions of the spine, and the coefficients of determination ranged between 0.75 and 0.88. The root-mean-square error was between 5° and 11°, and the mean difference was very close to 0. The area under the curve was excellent and significant, ranging between 95% and 99%. Conclusion The mathematical procedure presented is valid to evaluate the spinal inclination angle in photogrammetry, analogous to the Cobb angle in radiography.